Effect and Mechanisms of State Boredom on Consumers’ Livestreaming Addiction - Zhang, Nan; Li, Jian (Frontiers in Psychology, 2022)
With the rapid development of live streaming marketing in China, consumers spend increasingly time on watching and purchasing on the platform, showing a trend of live streaming addiction. In the early stage of the COVID-19 epidemic, the addiction has been exacerbated by a surge of boredom caused by home quarantine. Based on the observation of this phenomenon, this research focused on whether state boredom could facilitate consumers' live streaming addiction, and explored the associated mechanisms of this relationship. Based on three studies, this research found that state boredom had positive effect on consumers’ live streaming addiction, and this relationship worked through the mediating effect of consumers' sensation-seeking. We further verified a moderated mediation effect of consumers’ life meaning perception, where the indirect effect of state boredom on consumers’ live streaming addiction via consumers’ sensation seeking existed for high and low level of life meaning perception, but in opposite directions. The conclusions provided theoretically and practically implications for live streaming marketing and healthy leisure consumption.